Debt choice, growth opportunities and corporate investment: Evidence from China - Ning Ding; Kalimullah Bhat; Khalil Jebran (Financial Innovation, 2020)
The study aims to investigate how relying on short-term debt may help Chinese listed firms to make efficient investment decisions and reduce overinvestment problem for low-growth firms. The study uses a large set of panel data of non-financial Chinese listed firms over the period 2007-2017 and, using the robust two-stage generalized method of moments, which is robust to unobserved heterogeneity of individual firms and addresses endogeneity issues. Findings show a positive relationship between growth and investment; this association is enhanced by leverage, especially for high-growth firms. This supports the view that short-term debt helps Chinese firms to make optimal use of leverage and therefore make better investment decisions. Furthermore, the results reveal that leverage plays a disciplining and monitoring role to reduce overinvestment incentive for low-growth firms. Overall, the study suggests that shareholders should consider short-term debt to mitigate the debt overhang problem and restrict the opportunistic behavior of managers, which can lead to efficient investment decisions. It also provides foreign investors insights about capital structure in China, and how it can help them make better investment decisions.
Keywords: 650; Chinese firms; Leverage; Growth; Investment